Material poverty and multiple deprivation in Britain: the distinctiveness of multidimensional assessment. (30th January 2015) - Hick, Rod
Abstract: Poverty analysis is currently undergoing a multidimensional turn, increasingly focusing on the many ways in which human life can be impoverished and not just on material poverty. In this paper, we present an analysis of material poverty and multiple deprivation in Britain, which is inspired by the capability approach. We argue that the additional complexity of multidimensional analysis requires that it provides some insight not achieved by a more straightforward approach focusing on material poverty alone. Our findings indicate that whether a multidimensional assessment identifies different people as being in poverty depends on whether our interest is in identifying vulnerable individuals or in identifying vulnerable groups and whether we focus on dimensions in aggregate or disaggregate forms. We find that, although material poverty and multiple deprivation identify very different individuals, they display greater congruence in terms of identifying vulnerable groups, especially where aggregate measures are used.